أنماط التنشئة الأسرية وعلاقتها بأساليب الضبط المدرسي "دراسة ميدانية على طلبة المدارس الثانوية في مدينة اللاذقية" - الشمّاس, عيسى; الأخرس, سمية (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت هذه الدراسة إلى التعرف على أنماط التنشئة الأسرية السائدة لدى طلبة المدارس الثانوية، وعلاقتها بأساليب الضبط المدرسي في مدينة اللاذقية، وذلك من خلال الإجابة عن الأسئلة الآتية: 1- ما أنماط التنشئة الأسرية السائدة لدى طلبة المدارس الثانوية من وجهة نظر الطلبة؟ 2- ما أساليب الضبط المدرسي لدى طلبة المدارس الثانوية من وجهة نظر الطلبة؟ 3- هل هناك فروق ذات دلالة إحصائية عند مستوى الدلالة (0.05) في أنماط التنشئة الأسرية السائدة لدى طلبة المدارس الثانوية تعزى لمتغير الجنس؟ 4- هل هناك علاقة بين أنماط التنشئة الأسرية لدى طلبة المدارس الثانوية وأساليب الضبط المدرسي لديهم؟ ولتحقيق هدف الدراسة قامت الباحثة بتصميم استبانتين إحداهما لأنماط التنشئة الأسرية السائدة لدى طلبة المدارس الثانوية والأخرى لأساليب الضبط المدرسي تم تطبيقهما على عينة من طلبة الصف الأول الثانوي في مدينة اللاذقية وبلغ عدد أفراد العينة (124) طالباً وطالبةً. حيث أظهرت نتائج الدراسة ما يأتي: - أن أكثر أنماط التنشئة الأسرية السائدة لدى الطلبة في المجتمع السوري هو النمط الديمقراطي. - إن أكثر أساليب الضبط المدرسي شيوعاً هو أسلوب المكآفات. - توجد فروق ذات دلالة إحصائية في أنماط التنشئة الأسرية لصالح الإناث في النمط الديمقراطي ولصالح الذكور في النمطين التسلطي والإهمال. - توجد علاقة ذات دلالة إحصائية بين أنماط التنشئة الأسرية وأساليب الضبط المدرسي. The study aimed to identify the family nurture patterns prevailing among secondary school students and their relationship to the methods of school discipline by answering the following questions: 1- What are the family nurture Patterns for high school students from the students' point of view? 2- What are the school control methods for high school students from the students' point of view? 3- Are there any significant discrepancies in the level of statistical significance (0.05) in the family nurture patterns prevailing among high school students Education according to: the gender of the students? - Is there a relationship between methods of school discipline in high school and their family nurture patterns? In order to achieve the purpose of the study, the researcher designed two questionnaires, one was for the family nurture patterns prevailing among students of the secondary schools in Lattakia City, whereas the other questionnaire was designed for the school discipline methods, which applied on a sample which applied on a sample consisted, The sample were (124) student, male and female. -The conclusion and findings of the study were as follows: -The democratic pattern is the most common family nurture pattern prevailing among students in the Syria community. The discipline pattern is the most common in the rewards.- -Discrepancies of statistical significance in family nurture patterns were in favor of females in the democratic pattern and were in favor of males in the authoritarianism and negligence patterns.-There is relationship of statistical significance among family nurturing patterns and the school discipline methods.